Analysing the role of corporate social responsibility in determining firm value - Kabir, Musa Usman; Aripin, Norhani; Al-Dhamari, Redhwan Ahmed Ali (School of Social Sciences, USM, 2017)
Business entities are basically established to maximize wealth in order to create additional value for their owners. The concept of corporate social responsibility presupposes that corporate bodies should not only be concerned with shareholders wealth maximization but should equally care for the need of other noninvesting stakeholders. Hence, to ensured long-term value for corporate firms, attention should be tailored at satisfying the needs of both investing and non-investing stakeholders. Stakeholder’s welfare in overall enhanced corporate valuation. This paper highlight the takeholder’s theory as the underpinning theory of the study.